Comparative Analysis of Video Surveillance Regulation in Data Protection Laws in the Former Yugoslav States - Krivokapić, Đorđe; Krivokapić, Danilo; Adamović, Jelena; Stefanović, Aleksandra (Journal of Regional Security, 2021)
Video surveillance, the monitoring of a specific area, event, activity or person through an electronic device or a system for visual monitoring is already established as a central tool of public security policy. Video surveillance represents a starting point for implementing advanced technologies such as automatic number plate recognition (ANPR) and automatic facial recognition (AFR), which tend to become standards in many urban areas. Based on the increased use of video surveillance technologies, governments and private actors’ capabilities in terms of monitoring of the population and potentially violating fundamental human rights are colossally increased. The article will provide a comparative analysis of national regulatory frameworks of video surveillance in public spaces in former Yugoslav states and its compliance with standards provided by new data protection regulatory framework, particularly General Data Protection Regulation (GDPR). The article will also give an overview of the major violations of the right to privacy by video surveillance and insight into and potential impact of new projects and technologies currently under deployment in the observed countries.
Keywords: surveillance; facial recognition; privacy; regulatory framework; former Yugoslav states